Strategi Kepala Madrasah sebagai Pemimpin dalam Meningkatkan Mutu Pendidikan di Madrasah Ibtidaiyah Negeri Singkawang - Marsiyeh Marsiyeh; Aslan Aslan; Nilhakim Nilhakim (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research is motivated by the increasing demand for quality madrasa education and the need for leadership from madrasa principals capable of ensuring comprehensive quality in accordance with the eight National Education Standards (SNP). The purpose of this study is to describe the strategies of madrasa principals as leaders in improving educational quality at the Singkawang State Elementary Madrasah (MIN) based on the eight SNP framework. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews, direct observation of learning activities and madrasa management, and documentation studies of programs, learning materials, and other supporting documents. Research informants included the madrasa principal, the vice-curriculum supervisor, teachers, and parents. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, with validity checked using source and technique triangulation. The results indicate that quality improvement is carried out systematically and is interconnected across standards. In the graduate competency standards, madrasa principals target holistic outputs encompassing academic achievement, skills, piety, and morals. In the content standards, the implementation of the Independent Curriculum is monitored to ensure curriculum flexibility and effective differentiated learning. Process standards are strengthened through scheduled and spontaneous academic supervision, monitoring of teaching materials, utilization of technology, and active-collaborative learning. Quality improvement is also supported by improving the competency of educators and education personnel through ongoing training, performance assessments, learning communities, and coaching. For infrastructure, madrasas implement the Learning Environment and Facilities Preparation (PPLFB) program based on evaluation and improvement.